2005
DOI: 10.1159/000089145
|View full text |Cite
|
Sign up to set email alerts
|

Atrophic Gastritis Is Associated with Increased Sucrose Permeability Related to Chronic Inflammation

Abstract: Background: Different theories have been presented to explain how atrophic gastritis may lead to gastric cancer development. One contributing factor could be impaired function of the gastric mucosal barrier. The aim of this study was to investigate if there are changes in gastric mucosal permeability to sucrose in atrophic gastritis.Methods: The study comprised 22 patients with atrophic gastritis and 21 normal controls. Gastritis was classified according to the Sydney system from endoscopic biopsies of the gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Subsequently, several studies showed that abnormal gastroduodenal permeability to sucrose is a reasonable marker for the presence of gastroduodenal injury in NSAID users (DeMeo, 1995; Erlacher et al, 1998; Meddings et al, 1995; Smecuol et al, 2001; Sutherland et al, 1994). Other researchers used sucrose permeability tests to assess damage to the gastroduodenal mucosa induced by oral corticosteroids (Kiziltas et al, 1998), intense exercise (Lambert et al, 2007b; Pals et al, 1997; Smetanka et al, 1999), Helicobacter pylori infection (Borch et al, 1998; Goodgame et al, 1997), atrophic gastritis (Sjostedt Zsigmond et al, 2005), Crohn’s disease (Wyatt et al, 1997), celiac disease (Smecuol et al, 1997; Vogelsang et al, 1996), coffee (Cibickova et al, 2004), smoking (Gotteland et al, 2002) or a combination of these damaging factors (Gotteland et al, 2002; Lambert et al, 2007a; Lambert et al, 2001; Rabassa et al, 1996; Ryan et al, 1996; Santucci et al, 1995). …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several studies showed that abnormal gastroduodenal permeability to sucrose is a reasonable marker for the presence of gastroduodenal injury in NSAID users (DeMeo, 1995; Erlacher et al, 1998; Meddings et al, 1995; Smecuol et al, 2001; Sutherland et al, 1994). Other researchers used sucrose permeability tests to assess damage to the gastroduodenal mucosa induced by oral corticosteroids (Kiziltas et al, 1998), intense exercise (Lambert et al, 2007b; Pals et al, 1997; Smetanka et al, 1999), Helicobacter pylori infection (Borch et al, 1998; Goodgame et al, 1997), atrophic gastritis (Sjostedt Zsigmond et al, 2005), Crohn’s disease (Wyatt et al, 1997), celiac disease (Smecuol et al, 1997; Vogelsang et al, 1996), coffee (Cibickova et al, 2004), smoking (Gotteland et al, 2002) or a combination of these damaging factors (Gotteland et al, 2002; Lambert et al, 2007a; Lambert et al, 2001; Rabassa et al, 1996; Ryan et al, 1996; Santucci et al, 1995). …”
Section: Introductionmentioning
confidence: 99%
“…Sucrose, a disaccharide of glucose and fructose, is not absorbed through the mucosa of an intact GI tract, but may be absorbed in the presence of barrier breakdown, such as ulcers, inflammation and atrophic gastritis [10,11]. It is presumed that as with sucrose, maltodextrin-or a smaller oligosaccharide metabolite or maltose-may be absorbed by passive diffusion in the setting of gastric inflammation.…”
Section: Discussionmentioning
confidence: 99%